Unveiling factors influencing choice of clean cooking solutions among households: a systematic review of literature - Ocen, Samuel; Nkurunziza, Gideon; Bagire, Vincent; Echegu, Simon; Ssekakubo, Johnson; Atukunda, Ronnette (Frontiers in Sustainability, 2024)
Nearly half of the global population rely on solid polluting fuels such as firewood, charcoal, animal and plant wastes for cooking. Continued reliance on such fuels and technologies has severe negative health, environmental, and development impacts. Using a systematic literature review methodology, this study sought to unveil factors influencing choice of clean cooking solutions among households. This study adopted a systematically literature review approach to systematically identify, evaluate and synthesize articles in the field of clean cooking solutions. Systematic literature review is a rigorous and replicable methodology that is designed to identify, appraise and synthesize already existing literature on specific question or sub questions. In this study, the procedures suggested by Liberati et al. and Moher et al. based on preferred reporting items for systematic reviews and meta-analysis (PRISMA) approach. Seventy-four articles were synthesized and many factors influencing the choice of cooking solutions were identified alongside the existing gaps.